Immortalized stem cell-derived hepatocyte-like cells: An alternative model for studying dengue pathogenesis and therapy - Kongmanas, Kessiri; Punyadee, Nuntaya; Wasuworawong, Kasima; Songjaeng, Adisak; Prommool, Tanapan; Pewkliang, Yongyut; Manocheewa, Siriphan; Thiemmeca, Somchai; Sa-ngiamsuntorn, Khanit; Puttikhunt, Chunya; Faull, Kym Francis; Hongeng, Suradej; et al. (PLOS Neglected Tropical Diseases, 2020)
Suitable cell models are essential to advance our understanding of the pathogenesis of liver diseases and the development of therapeutic strategies. Primary human hepatocytes (PHHs), the most ideal hepatic model, are commercially available, but they are expensive and vary from lot-to-lot which confounds their utility. We have recently developed an immortalized hepatocyte-like cell line (imHC) from human mesenchymal stem cells, and tested it for use as a substitute model for hepatotropic infectious diseases. With a special interest in liver pathogenesis of viral infection, herein we determined the suitability of imHC as a host cell target for dengue virus (DENV) and as a model for anti-viral drug testing. We characterized the kinetics of DENV production, cellular responses to DENV infection (apoptosis, cytokine production and lipid droplet metabolism), and examined anti-viral drug effects in imHC cells with comparisons to the commonly used hepatoma cell lines (HepG2 and Huh-7) and PHHs. Our results showed that imHC cells had higher efficiencies in DENV replication and NS1 secretion as compared to HepG2 and Huh-7 cells. The kinetics of DENV infection in imHC cells showed a slower rate of apoptosis than the hepatoma cell lines and a certain similarity of cytokine profiles to PHHs. In imHC, DENV-induced alterations in levels of lipid droplets and triacylglycerols, a major component of lipid droplets, were more apparent than in hepatoma cell lines, suggesting active lipid metabolism in imHC. Significantly, responses to drugs with DENV inhibitory effects were greater in imHC cells than in HepG2 and Huh-7 cells. In conclusion, our findings suggest superior suitability of imHC as a new hepatocyte model for studying mechanisms underlying viral pathogenesis, liver diseases and drug effects.